Упрочнение валков прокатного стана титановыми покрытиями в условиях СВС - Середа, Борис Петрович; Палехова, Ирина Владимировна (НТУ "ХПИ", 2017)
Рассмотрены результаты исследований процессов нанесения многокомпонентных титановых покрытий в режиме теплового самовоспламенения на углеродистых сталях. С помощью методов математического моделирования разработаны оптимальные составы СВС-смесей для нанесения комплексных покрытий. Изучено влияние составов реакционных смесей на свойства полученных покрытий. Приведена схема формирования защитных покрытий. Установлены кинетические и теплофизические закономерности роста слоев. Представлены результаты микроскопического и рентгеноструктурного анализов фазового состава полученных покрытий, выполнен анализ их качественных характеристик.

The results of researches of processes of causing of multicomponent titanic coverings are considered in the mode of thermal spontaneous combustion of self-propagating high temperature synthesis on carbon steels. A chart over of forming of coverings is brought with the use of chemical gas-transport reactions. By means of methods of mathematical design optimal compositions of SHS-mixture are worked out for causing of complex coverages. The analysis of meaningful parameters influencing on a structure and operating properties of coverages is presented. Kinetic and thermophysical conformities to law of height of protective layers are set. Results are presented microscopic and X-ray diffraction analyses of phase composition of the got coverings, the analysis of their quality descriptions is executed. On the basis of the got conformities to law of forming of layers and their operating descriptions powder-like compositions of reactionary SHS– mixture are worked out for work-hardening of steelworks. The offered compositions of mixtures were tested for the superficial work hardening of rollers of flatting mills. The conducted tests on a microhardness and inoxidizability showed the improvement of descriptions of superficial layer.
Strengthening rolls of rolling mill with titanium coatings in SHS conditions
Keywords: реакция химическая; реакция газотранспортная; синтез высокотемпературный; синтез самораспространяющийся; самовоспламенение; диффузия; плотность; микротвердость; chemical gas-transport reactions; high temperature synthesis; spontaneous combustion; diffusion; closeness; microhardness